Plasma levels of miR‐29b and miR‐200b in type 2 diabetic retinopathy. Issue 2 (23rd November 2018) - Dantas da Costa e Silva, Maria Enoia; Polina, Evelise Regina; Crispim, Daisy; Sbruzzi, Renan Cesar; Lavinsky, Daniel; Mallmann, Felipe; Martinelli, Nidiane Carla; Canani, Luis Henrique; dos Santos, Katia Gonçalves
Abstract: MicroRNAs (miRNAs/miRs) are involved in the pathogenesis of diabetes mellitus and its chronic complications, and their circulating levels have emerged as potential biomarkers for the development and progression of diabetes. However, few studies have examined the expression of miRNAs in diabetic retinopathy (DR) in humans. This case‐control study aimed to investigate whether the plasma levels of miR‐29b and miR‐200b are associated with DR in 186 South Brazilians with type 2 diabetes (91 without DR, 46 with non‐proliferative DR and 49 with proliferative DR). We also included 20 healthy blood donors to determine the miRNA expression in the general population. Plasma levels of miR‐29b and miR‐200b were quantified by reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR). Proliferative DR was inversely associated with plasma levels of miR‐29b (unadjusted OR = 0.694, 95% CI: 0.535‐0.900, P  = 0.006) and miR‐200b (unadjusted OR = 0.797, 95% CI: 0.637‐0.997, P  = 0.047). However, these associations were lost after controlling for demographic and clinical covariates. In addition, patients with type 2 diabetes had lower miR‐200b levels than blood donors. Our findings reinforce the importance of addressing the role of circulating miRNAs, including miR‐29 and miR‐200b, in DR.